2017
DOI: 10.1371/journal.pone.0169653
|View full text |Cite
|
Sign up to set email alerts
|

Increased PD-1 Expression and Altered T Cell Repertoire Diversity Predict Mortality in Patients with Septic Shock: A Preliminary Study

Abstract: Sepsis causes impairment of innate and adaptive immunity by multiple mechanisms, including depletion of immune effector cells and T cell exhaustion. Although lymphocyte dysfunction is associated with increased mortality and potential reactivation of latent viral infection in patients with septic shock, the relation between viral reactivation and lymphocyte dysfunction is obscure. The objectives of this study were 1) to determine the relation of lymphocyte dysfunction to viral reactivation and mortality, and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 39 publications
4
29
2
2
Order By: Relevance
“…Prior studies among nonburned septic patients show that lymphopenia, upregulation of PD‐1 on T cells and PD‐L1 on monocytes correlate with increased susceptibility to secondary infections, viral reactivation, and increased mortality . We observed a significant decline in lymphocyte numbers in mice with burn wound sepsis.…”
Section: Discussionsupporting
confidence: 52%
“…Prior studies among nonburned septic patients show that lymphopenia, upregulation of PD‐1 on T cells and PD‐L1 on monocytes correlate with increased susceptibility to secondary infections, viral reactivation, and increased mortality . We observed a significant decline in lymphocyte numbers in mice with burn wound sepsis.…”
Section: Discussionsupporting
confidence: 52%
“…32 In patients following septic shock, TCR diversity is reduced and normalization of TCR diversity and PD-1 expression was reported to positively correlate with survival. 33 In patients with hepatitis C virus (HCV) infection, Miles and colleagues observed that TCR repertoire diversity is associated with HCV clearance. 34 Hence, TCR diversity is associated with a greater likelihood of a competent immune recognition, which is not restricted to foreign pathogens, with important consequences for cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This feedback loop would explain why a high degree of viral reactivation (of all viruses) correlates with increased mortality. It is still unclear whether elevated viral loads of herpesviruses following reactivation indeed impairs lymphocyte function or whether it is just a side effect of other kinds of immune suppression already taking place ( 238 ). It has been demonstrated that CMV infection can have an effect on the differentiation of immature lymphocytes into effector CD8 T cells; however, the overall effects this may have on the patient are not well-characterised ( 239 , 240 ).…”
Section: The Immunology Of Viral Sepsismentioning
confidence: 99%